2012
DOI: 10.2478/v10178-012-0063-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Advanced Signal-Processing Methods for Roller Bearing Faults Detection

Abstract: Wind turbines are nowadays one of the most promising energy sources. Every year, the amount of energy produced from the wind grows steadily. Investors demand turbine manufacturers to produce bigger, more efficient and robust units. These requirements resulted in fast development of condition-monitoring methods. However, significant sizes and varying operational conditions can make diagnostics of the wind turbines very challenging. The paper shows the case study of a wind turbine that had suffered a serious… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…The propagation of fault is shown in the frequency band. In their literature, Sun and Tang 22 and Urbanek et al 23 proposed an improvement of sensitivity of envelope spectra. The modulating signal may contain several parts as it is difficult to diagnose the fault.…”
Section: Technical Backgroundmentioning
confidence: 99%
“…The propagation of fault is shown in the frequency band. In their literature, Sun and Tang 22 and Urbanek et al 23 proposed an improvement of sensitivity of envelope spectra. The modulating signal may contain several parts as it is difficult to diagnose the fault.…”
Section: Technical Backgroundmentioning
confidence: 99%
“…Short-time Fourier transform (STFT), wavelet transform (WT) and Wigner-Ville distribution (WVD) are commonly used to convert the non-stationary signals into a time-frequency domain [2,3]. Urbanek et al [4] compared the effectiveness of various frequency domain-based signal processing techniques for detecting the faults in a roller bearing. They have concluded that the method using spectral coherence for narrowband envelope analysis was found to be effective in detecting the faults.…”
Section: Introductionmentioning
confidence: 99%
“…However, bearings inevitably degenerate and break down due to an overload of repetitive work. According to statistics, 30 percent of faults in rolling machinery originate from bearing faults; therefore, bearing fault prognostics is an important area of research [2][3][4][5]. Recently, studies on bearing faults prognostics have focused on fault signal feature extraction and fault classification.…”
Section: Introductionmentioning
confidence: 99%